Chronic Viral Infection Compromises the Quality of Circulating Mucosal–Associated Invariant T Cells and Follicular T Helper Cells via Expression of Inhibitory Receptors - Jaisheela Vimali; Yean K. Yong; Amudhan Murugesan; Hong Y. Tan; Ying Zhang; Rajeev Ashwin; Sivadoss Raju; Pachamuthu Balakrishnan; Marie Larsson; Vijayakumar Velu; Esaki M. Shankar (Frontiers in Bioscience-Landmark, 2024)
Background: Chronic viral infection results in impaired immune responses rendering viral persistence. Here, we compared the quality of T-cell responses among chronic hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV)-infected individuals by examining the levels of expression of selected immune activation and exhaustion molecules on circulating MAIT cells and Tfh cells. Methods: Cytokines were measured using a commercial Bio-plex Pro Human Cytokine Grp I Panel 17-plex kit (BioRad, Hercules, CA, USA). Inflammation was assessed by measuring an array of plasma cytokines, and phenotypic alterations in CD4+ T cells including circulating Tfh cells, CD8+ T cells, and TCR iVα7.2+ MAIT cells in chronic HBV, HCV, and HIV-infected patients and healthy controls. The cells were characterized based on markers pertaining to immune activation (CD69, ICOS, and CD27) proliferation (Ki67), cytokine production (TNF-α, IFN-γ) and exhaustion (PD-1). The cytokine levels and T cell phenotypes together with cell markers were correlated with surrogate markers of disease progression. Results: The activation marker CD69 was significantly increased in CD4+hi T cells, while CD8+ MAIT cells producing IFN-γ were significantly increased in chronic HBV, HCV and HIV infections. Six cell phenotypes, viz., TNF-α+CD4+lo T cells, CD69+CD8+ T cells, CD69+CD4+ MAIT cells, PD-1+CD4+hi T cells, PD-1+CD8+ T cells, and Ki67+CD4+ MAIT cells, were independently associated with decelerating the plasma viral load (PVL). TNF-α levels showed a positive correlation with increase in cytokine levels and decrease in PVL. Conclusion: Chronic viral infection negatively impacts the quality of peripheral MAIT cells and Tfh cells via differential expression of both activating and inhibitory receptors.